THE CHANGING PARADIGM OF INDONESIAN JIHADIST MOVEMENTS: From al-`Aduww al-Qarib to al-`Aduww al-Ba`id (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
Like in any other Muslim countries, an analysis of Islamic space in Indonesia cannot ignore the jihadist movements that took shape there. Since the reformation era, Indonesians have witnessed a number of bloody tragedies, ranging from religious conflicts in Ambon, attacks to the Western embassies offices, to the deadliest suicide bombings in Bali. All aforementioned attacks entails that a terrorist group operating in Southeast Asia called Jama’ah Islamiyyah does exist. The article deals with the historical account of the transformation of Indonesian jihadist movements. It will discuss, first, the intellectual roots of the emergence of transnational jihadist movements and, second, the Indonesian’ links to the trend as Jamaah Islamiyyah has demonstrated. The “near enemy” (al-‘aduww al-qarīb) and the “far enemy” (al-‘aduww al-ba‘īd) developed by Greges are key notions quoted as analytical tools to deal with diverse acts of jihadist movement in responde to the local and global parties perceived as anti-Islam.